Amour, sexe et mobylette - Bazzoli, Maria Silvia; Lelong, Christian (France : Cinedoc Films & Fechner Media, 2008)
How is love expressed in Africa today when you are twenty, forty or sixty? How is desire articulated and how does sexuality work? ”Love, Sex and Moped” ventures to explore how love is imagined or constructed, understood and thought of, how it was forged in childhood and how it survives and adapts to everyday constraints. This film is a collection of interviews where both men and women, young and old and with different backgrounds and diverse interests, share their vision about love, marriage, family and AIDS.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films